OCA (Optical Clear Adhesive) with high creep property, low storage modulus and self-repairing function and preparation method thereof
By introducing dynamically crosslinkable oxime urethane bonds into OCA optical glue, the problems of creases, bubbles, stacking and layering that existing OCA optical glues in the long-term use of folding screens are solved, and OCA optical glue with high flexibility, low energy storage modulus and self-repair functions are achieved, extending the service life of the folding display screen and reducing maintenance costs.
Patent Information
- Application Number
- CN202510220770.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-27
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2045-02-27
AI Technical Summary
The existing flexible OCA optical adhesive has a high modulus, which leads to the folding screen being prone to creases, bubbles, stacking and layering when used in complex environments for a long time, making it difficult and costly to repair.
Develop an OCA optical glue with strong creep, low energy storage modulus and self-healing function, and improves its self-healing ability and adhesive properties by introducing an appropriate amount of dynamically crosslinkable oxime urethane bonds.
This OCA optical adhesive has good self-repair performance and adhesiveness without affecting the light transmittance, which can effectively extend the service life of the folded display and reduce maintenance costs.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of flexible OCA optical adhesive, and in particular to an OCA optical adhesive with strong creep property, low storage modulus and self-repairing function and a preparation method thereof. Background Art
[0002] As a new form of smartphone, foldable phones have obvious advantages in providing a large screen experience and easy portability. Due to their appearance design and sense of technology, they are favored by consumers and gradually become the mainstream of smartphones. The screen folding methods of foldable phones currently on the market include two-axis inward folding, two-axis outward folding and teardrop folding. Flexible optically clear adhesive (OCA) plays a key role in folding screens. Flexible OCA optical adhesive is an important material for bonding various functional modules of folding screens. In order to ensure that the folding screen remains soft and bendable after being bent for a long time, the flexible OCA optical adhesive needs to have both good creep recovery performance and good adhesion reliability with various functional modules.
[0003] The existing flexible OCA optical adhesive has a high modulus. As the number of folds increases, it is easy to cause screen wear and creases. Especially at the folding point, it may even cause the display function layers to delaminate, bubbles and bad pixels to appear, affecting the appearance and service life. Moreover, once these problems occur on the folding screen, it is difficult to repair and the repair cost is high, affecting consumers' user experience and purchasing choices.
[0004] Therefore, developing an OCA optical adhesive with good bending performance and self-repairing properties is of great significance for solving problems such as creases, bubbles, and lamination delamination that occur during long-term use of folding screens in complex environments.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The object of the present invention is to provide a flexible OCA optical adhesive and a preparation method thereof. The OCA optical adhesive of the present invention has strong creep resistance, low storage modulus and excellent self-repairing function, which can improve the service life and long-term reliability of the foldable display screen.
[0007] In order to achieve the above-mentioned object of the present invention, the first aspect of the present invention provides an OCA optical adhesive with strong creep resistance, low storage modulus and self-repairing function, comprising an acrylate prepolymer, an oxime amine prepolymer and a first initiator; The mass ratio of the oxime urethane prepolymer to the acrylate prepolymer is (1-5): (95-100); The oxime urethane prepolymer is mainly prepared by the reaction of trimethylhexamethylene diisocyanate and a dioxime compound.
[0008] In a specific embodiment of the present invention, the trimethyl hexamethylene diisocyanate includes at least one of 2,2,4-trimethyl-hexamethylene diisocyanate and 2,4,4-trimethyl-hexamethylene diisocyanate. Further, the trimethyl hexamethylene diisocyanate includes 2,2,4-trimethyl-hexamethylene diisocyanate and 2,4,4-trimethyl-hexamethylene diisocyanate in a mass ratio of 1: (0.5-2).
[0009] In a specific embodiment of the present invention, the dioxime compound includes at least one of dimethylglyoxime, 2,4-pentanedione dioxime and p-benzoquinone dioxime.
[0010] In a specific embodiment of the present invention, the molar ratio of the trimethylhexamethylene diisocyanate to the dioxime compound is 1: (0.95-1.05).
[0011] In a specific embodiment of the present invention, the acrylate prepolymer is mainly prepared by polymerization of acrylate monomers under the initiation of a second initiator; the acrylate monomers include the following components in parts by weight: 60 to 80 parts of 2-ethylhexyl acrylate, 5 to 10 parts of butyl acrylate and 10 to 20 parts of hydroxyl-containing acrylate.
[0012] In a specific embodiment of the present invention, the hydroxyl-containing acrylate includes at least one of 2-hydroxyethyl acrylate and 2-hydroxy-2-butyl acrylate.
[0013] In a specific embodiment of the present invention, the amount of the second initiator is 0.2wt% to 1wt% of the total amount of the acrylic ester monomer. Further, the second initiator includes at least one of 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenyl acetone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide and benzoin dimethyl ether.
[0014] In a specific embodiment of the present invention, the amount of the first initiator is 0.2wt% to 1wt% of the mass of the acrylate prepolymer and the oxime amine prepolymer. Further, the first initiator includes at least one of 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenyl acetone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide and benzoin dimethyl ether.
[0015] In a specific embodiment of the present invention, the thickness of the OCA optical adhesive is 25-200 μm.
[0016] The second aspect of the present invention provides a method for preparing the OCA optical adhesive of the first aspect of the present invention, comprising the following steps: mixing an acrylate prepolymer, an oxime urethane prepolymer and a first initiator in proportion, coating them into a film, and curing them by ultraviolet radiation.
[0017] Compared with the prior art, the present invention has the following beneficial effects: (1) The OCA optical adhesive of the present invention introduces an appropriate amount of dynamically cross-linkable oxime urethane bonds, which, while ensuring the light transmittance, endows the OCA optical adhesive with good self-repairing ability and improves the bonding performance between the OCA optical adhesive and the substrate, which is beneficial to improving the reworkability of the OCA optical adhesive during use; (2) The preparation of the OCA optical adhesive of the present invention is simple, the conditions are mild, no toxic or harmful substances are produced, and it is environmentally friendly; (3) Based on the high flexibility, high bending resistance, high weather resistance, strong creep resistance and self-healing performance of the OCA optical adhesive of the present invention, it can solve the problems of creases, bubbles, lamination and delamination that occur in the long-term use of folding display screens in complex environments, and can effectively extend its service life. DETAILED DESCRIPTION
[0018] The technical scheme of the present invention will be clearly and completely described below in conjunction with specific embodiments, but it will be appreciated by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work, all belong to the scope of protection of the present invention. If specific conditions are not indicated in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0019] In the description of the present invention, it should be noted that the terms “first” and “second” are only used for descriptive purposes and cannot be understood as indicating or implying relative importance.
[0020] The first aspect of the present invention provides an OCA optical adhesive with strong creep resistance, low storage modulus and self-repairing function, comprising an acrylate prepolymer, an oxime urethane prepolymer and a first initiator; The mass ratio of oxime urethane prepolymer to acrylate prepolymer is (1-5): (95-100); Oxime urethane prepolymer is mainly prepared by the reaction of trimethylol hexamethylene diisocyanate and dioxime compound.
[0021] The OCA optical adhesive of the present invention introduces an appropriate amount of dynamically cross-linkable oxime urethane bonds, which, while ensuring light transmittance, endows the OCA optical adhesive with good self-repairing ability and improves the bonding performance between the OCA optical adhesive and the substrate, which is beneficial to improving the reworkability of the OCA optical adhesive during use.
[0022] The oxime urethane bond is structurally stable at room temperature, and undergoes a reverse reaction when heated to produce free isocyanate groups (NCO) and oxime groups (NOH). The reversible dissociation and bonding give the OCA optical adhesive good fluidity and self-healing ability. The present invention regulates the mass ratio of the oxime urethane prepolymer to the acrylate prepolymer to be (1-5): (95-100), for example, 1:100, 1:99, 2:98, 3:97, 4:96, 5:95 or any two of them, thereby improving the self-healing performance of the OCA optical adhesive as well as the appropriate creep and bonding properties. The study found that when the dosage of oxime urethane prepolymer is too high, although good self-healing performance can be guaranteed, excessive oxime urethane prepolymer will cause the creep performance of OCA optical adhesive to deteriorate, and the increase in cross-linking density will increase the cohesive strength, thereby enhancing its bonding strength to the substrate, resulting in the OCA optical adhesive adhering to the surface of the substrate; when the dosage of oxime urethane prepolymer is too low, the self-healing performance is poor.
[0023] The oxime urethane prepolymer of the present invention is mainly prepared by reacting trimethyl hexamethylene diisocyanate with a dioxime compound. Trimethyl hexamethylene diisocyanate is a polymethyl-substituted aliphatic diisocyanate, which contains a relatively long methylene segment in its molecular structure and has low crystallinity. It can provide a flexible segment for the polymer, so that the prepared OCA optical adhesive has high flexibility and low storage modulus, thereby improving the bending resistance of the OCA optical adhesive.
[0024] Specifically, the oxime urethane bond in the oxime urethane prepolymer of the present invention is structurally stable at room temperature, and undergoes a reverse reaction when heated to produce free isocyanate groups and oxime groups, thereby increasing the density of short molecular chains and enhancing the mobility of molecular chains; and both isocyanate groups and oxime groups are strongly polar groups. Therefore, the introduction of the oxime urethane prepolymer into the OCA optical adhesive of the present invention and the introduction of oxime urethane bonds into the polymer network of the OCA optical adhesive can enable the adhesive to have good self-repairing properties without affecting the transmittance, and can also exhibit good adhesion between the functional modules of the folding display screen, and exhibit high flexibility, high bending resistance, high weather resistance, strong creep and self-repairing properties, thereby effectively improving the service life of the folding screen and maintaining long-term reliability for daily use.
[0025] In a specific embodiment of the present invention, trimethyl hexamethylene diisocyanate includes at least one of 2,2,4-trimethyl-hexamethylene diisocyanate and 2,4,4-trimethyl-hexamethylene diisocyanate. Further, trimethyl hexamethylene diisocyanate includes 2,2,4-trimethyl-hexamethylene diisocyanate and 2,4,4-trimethyl-hexamethylene diisocyanate in a mass ratio of 1: (0.5-2).
[0026] Among them, the structural formulas of 2,2,4-trimethyl-hexamethylene diisocyanate and 2,4,4-trimethyl-hexamethylene diisocyanate are as follows:
[0027] In a specific embodiment of the present invention, the dioxime compound includes at least one of dimethylglyoxime, 2,4-pentanedione dioxime and p-benzoquinone dioxime.
[0028] In a specific embodiment of the present invention, the molar ratio of trimethylhexamethylene diisocyanate to the dioxime compound is 1:(0.95-1.05), for example, 1:0.95, 1:0.98, 1:0.1, 1:1.02, 1:1.05 or a range consisting of any two of them.
[0029] In a specific embodiment of the present invention, the acrylate prepolymer is mainly prepared by polymerization of acrylate monomers under the initiation of a second initiator; the acrylate monomers include the following components in parts by weight: 60 to 80 parts of 2-ethylhexyl acrylate, 5 to 10 parts of butyl acrylate and 10 to 20 parts of hydroxyl-containing acrylate.
[0030] In a specific embodiment of the present invention, the hydroxyl-containing acrylate includes at least one of 2-hydroxyethyl acrylate and 2-hydroxy-2-butyl acrylate.
[0031] For example, in different embodiments, the amounts of the acrylic acid ester monomers may be as follows, in parts by weight: The amount of 2-ethylhexyl acrylate can be 60 parts, 65 parts, 70 parts, 75 parts, 80 parts or a range consisting of any two of them; The amount of butyl acrylate can be 5 parts, 6 parts, 8 parts, 10 parts or a range consisting of any two of them; The amount of the hydroxyl-containing acrylate can be 10 parts, 14 parts, 16 parts, 20 parts or a range consisting of any two of them.
[0032] In a specific embodiment of the present invention, in the acrylic ester monomers, the proportion of the hydroxyl-containing acrylic ester monomers is 10 wt % to 25 wt %.
[0033] In a specific embodiment of the present invention, the storage modulus of the OCA optical adhesive at -20°C is less than 30 KPa, and the storage modulus at 25°C is less than 3 KPa.
[0034] In a specific embodiment of the present invention, the creep recovery rate of the OCA optical adhesive at room temperature exceeds 90%, the maximum strain exceeds 300%, the creep recovery rate at -20°C exceeds 85%, and the maximum strain exceeds 90%.
[0035] In a specific embodiment of the present invention, the transmittance of the OCA optical adhesive is greater than 93%, and the haze is less than 0.12%.
[0036] In a specific embodiment of the present invention, the thickness of the OCA optical adhesive is 25 to 200 μm, but is not limited thereto and can be adjusted according to actual usage requirements. For example, it can be 25 μm, 50 μm, 75 μm, 100 μm, 125 μm, 150 μm, 175 μm, 200 μm or a range consisting of any two of them.
[0037] In a specific embodiment of the present invention, the reaction of trimethylhexamethylene diisocyanate and the dioxime compound needs to be carried out in the presence of a solvent and a catalyst.
[0038] In a specific embodiment of the present invention, the solvent is tetrahydrofuran; the amount of tetrahydrofuran used is 50% to 100% of the total mass of the reaction system, for example, it can be 50%, 60%, 70%, 80%, 90%, 100% or a range consisting of any two thereof. The total mass of the reaction system refers to the mass of trimethylhexamethylene diisocyanate and the dioxime compound.
[0039] In a specific embodiment of the present invention, the catalyst includes an organic tin catalyst; the amount of the organic tin catalyst is 0.02% to 0.1% of the total mass of the reaction system, for example, 0.02%, 0.05%, 0.08%, 0.1% or any two thereof.
[0040] In the present invention, the organic tin catalyst used in the reaction of trimethylhexamethylene diisocyanate with the dioxime compound includes but is not limited to at least one of dibutyltin diacetate, dibutyltin dilaurate and stannous octoate.
[0041] In a specific embodiment of the present invention, the preparation of oxime urethane prepolymer includes: dissolving trimethylhexamethylene diisocyanate and a dioxime compound in a solvent, adding a catalyst, and reacting at 60-120° C. under a protective atmosphere to obtain oxime urethane prepolymer.
[0042] For example, in different embodiments, in the preparation of the oxime urethane prepolymer, the reaction temperature can be 60° C., 80° C., 100° C., 120° C., or a range consisting of any two thereof. The specific reaction time is adjusted according to the infrared characteristic peak area of the isocyanate group in the reaction system, and the reaction is performed until the infrared characteristic peak area of the isocyanate group in the reaction system no longer changes.
[0043] In a specific embodiment of the present invention, the amount of the second initiator is 0.2 wt% to 1 wt% of the total amount of the acrylate monomer. Further, the second initiator includes at least one of 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenyl acetone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide and benzoin dimethyl ether.
[0044] In a specific embodiment of the present invention, the preparation of the acrylate prepolymer includes: the acrylate monomer reacts under the action of a second initiator under a protective atmosphere and under ultraviolet light irradiation to obtain the acrylate prepolymer. Furthermore, during the ultraviolet light irradiation, the wavelength of the ultraviolet light is 350 to 420 nm, and the energy of the ultraviolet light is 1500 to 4000 mj / cm 2 .
[0045] In a specific embodiment of the present invention, the amount of the first initiator is 0.2wt% to 1wt% of the mass of the acrylate prepolymer and the oxime amine ester prepolymer, for example, it can be 0.2wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.8wt%, 1wt% or any two thereof. Further, the first initiator includes at least one of 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenyl acetone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide and benzoin dimethyl ether.
[0046] The first initiator and the second initiator used in the present invention may be the same or different.
[0047] The second aspect of the present invention provides a method for preparing the OCA optical adhesive of the first aspect of the present invention, comprising the following steps: mixing an acrylate prepolymer, an oxime urethane prepolymer and a first initiator in proportion, coating them into a film, and curing them by ultraviolet radiation.
[0048] In a specific embodiment of the present invention, during radiation curing, the wavelength of the ultraviolet light is 350 to 420 nm, for example, 350 nm, 365 nm, 380 nm, 400 nm, 405 nm, 420 nm or any two thereof, and the energy of the ultraviolet light is 1500 to 4000 mj / cm 2 , for example, 1500 mj / cm 2 、2000mj / cm 2、2500mj / cm 2 、3000mj / cm 2 、3500mj / cm 2 、4000mj / cm 2 Or a range consisting of any two of them.
[0049] The coating method of the present invention is not limited, for example, manual coating or machine coating can be used, and the specific coating thickness can be conventionally adjusted according to the actual thickness requirement of the OCA optical adhesive.
[0050] The protective atmosphere involved in the present invention includes but is not limited to nitrogen atmosphere.
[0051] Some of the raw material information used in the following specific embodiments of the present invention may be as follows, but is not limited thereto: Trimethyl hexamethylene diisocyanate, purity 99%, Evonik, Germany, the mass ratio of 2,2,4-trimethyl hexamethylene diisocyanate and 2,4,4-trimethyl hexamethylene diisocyanate is 1:1; Isophorone diisocyanate, purity >99%, Wanhua Chemical; Dimethylglyoxime, purity >98%, MacLean.
[0052] Tetrahydrofuran, purity >99%, MacLean.
[0053] Before use, part of the raw materials may be dried and dehydrated, for example, by using 4A molecular sieves.
[0054] In the preparation of the oxime urethane prepolymers of the following embodiments of the present invention, Fourier transform infrared spectroscopy was used to qualitatively characterize the product structure; the specific instrument model was a Bruker Vector 33 FT-IR spectrometer, and the detection range was mainly 400 to 4000 cm -1 The extent of the reaction is detected by monitoring the changes in the infrared characteristic peak areas of the characteristic groups.
[0055] The preparation process of the oxime urethane prepolymer involved in the following embodiments includes the following route:
[0056] Example 1 This embodiment provides a method for preparing OCA optical adhesive, comprising the following steps: (1) Preparation of oxime urethane prepolymer: 52.57 g of trimethyl hexamethylene diisocyanate and 0.09 g of dibutyltin dilaurate were added to a 250 mL four-necked jacketed reactor. The reactor was filled with 50 mL of tetrahydrofuran solution and equipped with an electric stirrer, a thermometer, a nitrogen pipeline and a serpentine condenser. The equipment was connected and nitrogen was introduced into the reactor for 10 min to replace the dissolved oxygen in the reactor. At the same time, the electric stirrer was started at a speed of 300 rpm to stir the reactants in the reactor evenly. The reaction temperature was controlled at 80 °C. After the temperature was constant, 29.03 g of dimethylglyoxime was added to the reactor. After dimethylglyoxime was completely dissolved, samples were taken every 30 min and the reaction was continued until the concentration at 2268 cm in the infrared spectrum was reached. -1 When the infrared characteristic peak area of NCO no longer changes, the reaction is stopped to obtain an oxime urethane prepolymer.
[0057] (2) Preparation of acrylate prepolymer: 65 parts by weight of 2-ethylhexyl acrylate, 10 parts by weight of butyl acrylate, 10 parts by weight of 2-hydroxyethyl acrylate, 10 parts by weight of 2-hydroxy-2-butyl acrylate and 0.2 parts by weight of 1-hydroxycyclohexyl phenyl ketone were added to a reactor equipped with an electric stirrer, a thermometer, a nitrogen pipeline and a dry air pipeline. The equipment was connected and nitrogen was introduced into the reactor for 10 minutes to replace the dissolved oxygen in the reactor. At the same time, the electric stirrer was started at a speed of 300 rpm to stir the reactants in the reactor evenly. A high-pressure UV mercury lamp was used to irradiate the reactor at 1500 mj / cm 2 Energy irradiation, when the reaction temperature rises to 25-40°C (such as 25°C), stop irradiation, turn off nitrogen, and introduce dry air until the polymer temperature begins to drop, thereby obtaining an acrylate prepolymer.
[0058] (3) Preparation of OCA optical adhesive: Take 5 parts of oxime urethane prepolymer, 95 parts of acrylate prepolymer and 0.6 parts of 1-hydroxycyclohexyl phenyl ketone by weight, mix them evenly, degas in vacuum, and then apply the mixture between the light and heavy layers of polyethylene terephthalate (PET) release film. Use a high-pressure UV mercury lamp at 2000mj / cm 2 Energy irradiation, reaction to 810cm in infrared spectrum -1 Until the characteristic peak of the nearby acrylate double bond disappears, OCA optical glue with a thickness of 50μm is obtained.
[0059] Example 2 This embodiment provides a method for preparing OCA optical adhesive, comprising the following steps: (1) Preparation of oxime urethane prepolymer: 52.57 g of trimethyl hexamethylene diisocyanate and 0.09 g of dibutyltin dilaurate were added to a 250 mL four-necked jacketed reactor. The reactor was filled with 50 mL of tetrahydrofuran solution and equipped with an electric stirrer, a thermometer, a nitrogen pipeline and a serpentine condenser. The equipment was connected and nitrogen was introduced into the reactor for 10 min to replace the dissolved oxygen in the reactor. At the same time, the electric stirrer was started at a speed of 300 rpm to stir the reactants in the reactor evenly. The reaction temperature was controlled at 80 °C. After the temperature was constant, 29.03 g of dimethylglyoxime was added to the reactor. After dimethylglyoxime was completely dissolved, samples were taken every 30 min and the reaction was continued until the concentration at 2268 cm in the infrared spectrum was reached. -1 When the infrared characteristic peak area of NCO no longer changes, the reaction is stopped to obtain an oxime urethane prepolymer.
[0060] (2) Preparation of acrylate prepolymer: 67 parts by weight of 2-ethylhexyl acrylate, 10 parts by weight of butyl acrylate, 10 parts by weight of 2-hydroxyethyl acrylate, 10 parts by weight of 2-hydroxy-2-butyl acrylate and 0.2 parts by weight of 1-hydroxycyclohexyl phenyl ketone were added to a reactor equipped with an electric stirrer, a thermometer, a nitrogen pipeline and a dry air pipeline. The equipment was connected and nitrogen was introduced into the reactor for 10 minutes to replace the dissolved oxygen in the reactor. At the same time, the electric stirrer was started at a speed of 300 rpm to stir the reactants in the reactor evenly. A high-pressure UV mercury lamp was used to irradiate the reactor at 1500 mj / cm 2 Energy irradiation, when the reaction temperature rises to 25-40°C (such as 25°C), stop irradiation, turn off nitrogen, and introduce dry air until the polymer temperature begins to drop, thereby obtaining an acrylate prepolymer.
[0061] (3) Preparation of OCA optical adhesive: Take 3 parts of oxime urethane prepolymer, 97 parts of acrylate prepolymer and 0.6 parts of 1-hydroxycyclohexyl phenyl ketone by weight, mix them evenly, degas in vacuum, and then apply the mixture between the light and heavy layers of polyethylene terephthalate (PET) release film. Use a high-pressure UV mercury lamp at 2000mj / cm 2 Energy irradiation, reaction to 810cm in infrared spectrum -1 Until the characteristic peak of the nearby acrylate double bond disappears, OCA optical glue with a thickness of 50μm is obtained.
[0062] Example 3 This embodiment provides a method for preparing OCA optical adhesive, comprising the following steps: (1) Preparation of oxime urethane prepolymer: 52.57 g of trimethyl hexamethylene diisocyanate and 0.09 g of dibutyltin dilaurate were added to a 250 mL four-necked jacketed reactor. The reactor was filled with 50 mL of tetrahydrofuran solution and equipped with an electric stirrer, a thermometer, a nitrogen pipeline and a serpentine condenser. The equipment was connected and nitrogen was introduced into the reactor for 10 min to replace the dissolved oxygen in the reactor. At the same time, the electric stirrer was started at a speed of 300 rpm to stir the reactants in the reactor evenly. The reaction temperature was controlled at 80 °C. After the temperature was constant, 29.03 g of dimethylglyoxime was added to the reactor. After dimethylglyoxime was completely dissolved, samples were taken every 30 min and the reaction was continued until the concentration at 2268 cm in the infrared spectrum was reached. -1 When the infrared characteristic peak area of NCO no longer changes, the reaction is stopped to obtain an oxime urethane prepolymer.
[0063] (2) Preparation of acrylate prepolymer: 69 parts by weight of 2-ethylhexyl acrylate, 10 parts by weight of butyl acrylate, 10 parts by weight of 2-hydroxyethyl acrylate, 10 parts by weight of 2-hydroxy-2-butyl acrylate and 0.2 parts by weight of 1-hydroxycyclohexyl phenyl ketone were added to a reactor equipped with an electric stirrer, a thermometer, a nitrogen pipeline and a dry air pipeline. The equipment was connected and nitrogen was introduced into the reactor for 10 minutes to replace the dissolved oxygen in the reactor. At the same time, the electric stirrer was started at a speed of 300 rpm to stir the reactants in the reactor evenly. A high-pressure UV mercury lamp was used to irradiate the reactor at 1500 mj / cm 2 Energy irradiation, when the reaction temperature rises to 25-40°C (such as 25°C), stop irradiation, turn off nitrogen, and introduce dry air until the polymer temperature begins to drop, thereby obtaining an acrylate prepolymer.
[0064] (3) Preparation of OCA optical adhesive: Take 1 part of oxime urethane prepolymer, 99 parts of acrylate prepolymer and 0.6 parts of 1-hydroxycyclohexyl phenyl ketone by weight, mix them evenly, degas in vacuum, and then apply the mixture between the light and heavy layers of polyethylene terephthalate (PET) release film. Use a high-pressure UV mercury lamp at 2000mj / cm 2 Energy irradiation, reaction to 810cm in infrared spectrum -1 Until the characteristic peak of the nearby acrylate double bond disappears, OCA optical glue with a thickness of 50μm is obtained.
[0065] Example 4 This embodiment provides a method for preparing OCA optical adhesive, comprising the following steps: (1) Preparation of oxime urethane prepolymer: 52.57 g of trimethyl hexamethylene diisocyanate and 0.09 g of dibutyltin dilaurate were added to a 250 mL four-necked jacketed reactor. The reactor was filled with 50 mL of tetrahydrofuran solution and equipped with an electric stirrer, a thermometer, a nitrogen pipeline and a serpentine condenser. The equipment was connected and nitrogen was introduced into the reactor for 10 min to replace the dissolved oxygen in the reactor. At the same time, the electric stirrer was started at a speed of 300 rpm to stir the reactants in the reactor evenly. The reaction temperature was controlled at 80 °C. After the temperature was constant, 29.03 g of dimethylglyoxime was added to the reactor. After dimethylglyoxime was completely dissolved, samples were taken every 30 min and the reaction was continued until the concentration at 2268 cm in the infrared spectrum was reached. -1 When the infrared characteristic peak area of NCO no longer changes, the reaction is stopped to obtain an oxime urethane prepolymer.
[0066] (2) Preparation of acrylate prepolymer: 75 parts by weight of 2-ethylhexyl acrylate, 10 parts by weight of butyl acrylate, 5 parts by weight of 2-hydroxyethyl acrylate, 5 parts by weight of 2-hydroxy-2-butyl acrylate and 0.2 parts by weight of 1-hydroxycyclohexyl phenyl ketone were added to a reactor equipped with an electric stirrer, a thermometer, a nitrogen pipeline and a dry air pipeline. The equipment was connected and nitrogen was introduced into the reactor for 10 minutes to replace the dissolved oxygen in the reactor. At the same time, the electric stirrer was started at a speed of 300 rpm to stir the reactants in the reactor evenly. A high-pressure UV mercury lamp was used to irradiate the reactor at 1500 mj / cm 2 Energy irradiation, when the reaction temperature rises to 25-40°C (such as 25°C), stop irradiation, turn off nitrogen, and introduce dry air until the polymer temperature begins to drop, thereby obtaining an acrylate prepolymer.
[0067] (3) Preparation of OCA optical adhesive: Take 5 parts of oxime urethane prepolymer, 95 parts of acrylate prepolymer and 0.6 parts of 1-hydroxycyclohexyl phenyl ketone by weight, mix them evenly, degas in vacuum, and then apply the mixture between the light and heavy layers of polyethylene terephthalate (PET) release film. Use a high-pressure UV mercury lamp at 2000mj / cm 2 Energy irradiation, reaction to 810cm in infrared spectrum -1 Until the characteristic peak of the nearby acrylate double bond disappears, OCA optical glue with a thickness of 50μm is obtained.
[0068] Example 5 This embodiment provides a method for preparing OCA optical adhesive, comprising the following steps: (1) Preparation of oxime urethane prepolymer: 52.57 g of trimethyl hexamethylene diisocyanate and 0.09 g of dibutyltin dilaurate were added to a 250 mL four-necked jacketed reactor. The reactor was filled with 50 mL of tetrahydrofuran solution and equipped with an electric stirrer, a thermometer, a nitrogen pipeline and a serpentine condenser. The equipment was connected and nitrogen was introduced into the reactor for 10 min to replace the dissolved oxygen in the reactor. At the same time, the electric stirrer was started at a speed of 300 rpm to stir the reactants in the reactor evenly. The reaction temperature was controlled at 80 °C. After the temperature was constant, 29.03 g of dimethylglyoxime was added to the reactor. After dimethylglyoxime was completely dissolved, samples were taken every 30 min and the reaction was continued until the concentration at 2268 cm in the infrared spectrum was reached. -1 When the infrared characteristic peak area of NCO no longer changes, the reaction is stopped to obtain an oxime urethane prepolymer.
[0069] (2) Preparation of acrylate prepolymer: 77 parts by weight of 2-ethylhexyl acrylate, 10 parts by weight of butyl acrylate, 5 parts by weight of 2-hydroxyethyl acrylate, 5 parts by weight of 2-hydroxy-2-butyl acrylate and 0.2 parts by weight of 1-hydroxycyclohexyl phenyl ketone were added to a reactor equipped with an electric stirrer, a thermometer, a nitrogen pipeline and a dry air pipeline. The equipment was connected and nitrogen was introduced into the reactor for 10 minutes to replace the dissolved oxygen in the reactor. At the same time, the electric stirrer was started at a speed of 300 rpm to stir the reactants in the reactor evenly. A high-pressure UV mercury lamp was used to irradiate the reactor at 1500 mj / cm 2 Energy irradiation, when the reaction temperature rises to 25-40°C (such as 25°C), stop irradiation, turn off nitrogen, and introduce dry air until the polymer temperature begins to drop, thereby obtaining an acrylate prepolymer.
[0070] (3) Preparation of OCA optical adhesive: Take 3 parts of oxime urethane prepolymer, 97 parts of acrylate prepolymer and 0.6 parts of 1-hydroxycyclohexyl phenyl ketone by weight, mix them evenly, degas in vacuum, and then apply the mixture between the light and heavy layers of polyethylene terephthalate (PET) release film. Use a high-pressure UV mercury lamp at 2000mj / cm 2 Energy irradiation, reaction to 810cm in infrared spectrum -1 Until the characteristic peak of the nearby acrylate double bond disappears, OCA optical glue with a thickness of 50μm is obtained.
[0071] Example 6 This embodiment provides a method for preparing OCA optical adhesive, comprising the following steps: (1) Preparation of oxime urethane prepolymer: 52.57 g of trimethyl hexamethylene diisocyanate and 0.09 g of dibutyltin dilaurate were added to a 250 mL four-necked jacketed reactor. The reactor was filled with 50 mL of tetrahydrofuran solution and equipped with an electric stirrer, a thermometer, a nitrogen pipeline and a serpentine condenser. The equipment was connected and nitrogen was introduced into the reactor for 10 min to replace the dissolved oxygen in the reactor. At the same time, the electric stirrer was started at a speed of 300 rpm to stir the reactants in the reactor evenly. The reaction temperature was controlled at 80 °C. After the temperature was constant, 29.03 g of dimethylglyoxime was added to the reactor. After dimethylglyoxime was completely dissolved, samples were taken every 30 min and the reaction was continued until the concentration at 2268 cm in the infrared spectrum was reached. -1 When the infrared characteristic peak area of NCO no longer changes, the reaction is stopped to obtain an oxime urethane prepolymer.
[0072] (2) Preparation of acrylate prepolymer: 79 parts by weight of 2-ethylhexyl acrylate, 10 parts by weight of butyl acrylate, 5 parts by weight of 2-hydroxyethyl acrylate, 5 parts by weight of 2-hydroxy-2-butyl acrylate and 0.2 parts by weight of 1-hydroxycyclohexyl phenyl ketone were added to a reactor equipped with an electric stirrer, a thermometer, a nitrogen pipeline and a dry air pipeline. The equipment was connected and nitrogen was introduced into the reactor for 10 minutes to replace the dissolved oxygen in the reactor. At the same time, the electric stirrer was started at a speed of 300 rpm to stir the reactants in the reactor evenly. A high-pressure UV mercury lamp was used to irradiate the reactor at 1500 mj / cm 2 Energy irradiation, when the reaction temperature rises to 25-40°C (such as 25°C), stop irradiation, turn off nitrogen, and introduce dry air until the polymer temperature begins to drop, thereby obtaining an acrylate prepolymer.
[0073] (3) Preparation of OCA optical adhesive: Take 1 part of oxime urethane prepolymer, 99 parts of acrylate prepolymer and 0.6 parts of 1-hydroxycyclohexyl phenyl ketone by weight, mix them evenly, degas in vacuum, and then apply the mixture between the light and heavy layers of polyethylene terephthalate (PET) release film. Use a high-pressure UV mercury lamp at 2000mj / cm 2 Energy irradiation, reaction to 810cm in infrared spectrum -1 Until the characteristic peak of the nearby acrylate double bond disappears, OCA optical glue with a thickness of 50μm is obtained.
[0074] Comparative Example 1 Comparative Example 1 refers to the method for preparing the OCA optical adhesive of Example 3, except that in step (3), the amounts of oxime amine prepolymer and acrylate prepolymer used are different.
[0075] Step (3) of Comparative Example 1 comprises: taking 10 parts by weight of oxime urethane prepolymer, 90 parts by weight of acrylate prepolymer and 0.6 parts by weight of 1-hydroxycyclohexyl phenyl ketone, mixing them evenly, degassing them under vacuum, and then coating the mixture between the light and heavy layers of polyethylene terephthalate (PET) release film. Using a high-pressure UV mercury lamp at 2000 mj / cm 2 Energy irradiation, reaction to 810cm in infrared spectrum -1 Until the characteristic peak of the nearby acrylate double bond disappears, OCA optical glue with a thickness of 50μm is obtained.
[0076] Comparative Example 2 Comparative Example 2 provides a method for preparing OCA optical adhesive, comprising the following steps: (1) Preparation of acrylate prepolymer: 75 parts by weight of 2-ethylhexyl acrylate, 10 parts by weight of butyl acrylate, 5 parts by weight of 2-hydroxyethyl acrylate, 5 parts by weight of 2-hydroxy-2-butyl acrylate and 0.2 parts by weight of 1-hydroxycyclohexyl phenyl ketone were added to a reactor equipped with an electric stirrer, a thermometer, a nitrogen pipeline and a dry air pipeline. The equipment was connected and nitrogen was introduced into the reactor for 10 minutes to replace the dissolved oxygen in the reactor. At the same time, the electric stirrer was started at a speed of 300 rpm to stir the reactants in the reactor evenly. A high-pressure UV mercury lamp was used to irradiate the reactor at 1500 mj / cm 2 Energy irradiation, when the reaction temperature rises to 25-40°C (such as 25°C), stop irradiation, turn off nitrogen, and introduce dry air until the polymer temperature begins to drop, thereby obtaining an acrylate prepolymer.
[0077] (2) Preparation of OCA optical adhesive: Take 100 parts by weight of acrylate prepolymer and 0.6 parts of 1-hydroxycyclohexyl phenyl ketone, mix them evenly, degas under vacuum, and then apply the mixture between the light and heavy layers of polyethylene terephthalate (PET) release film. Use a high-pressure UV mercury lamp at 2000mj / cm 2 Energy irradiation, reaction to 810cm in infrared spectrum -1 Until the characteristic peak of the nearby acrylate double bond disappears, OCA optical glue with a thickness of 50μm is obtained.
[0078] Comparative Example 3 Comparative Example 3 provides a method for preparing OCA optical adhesive, comprising the following steps: (1) Preparation of acrylate prepolymer: 75 parts by weight of 2-ethylhexyl acrylate, 10 parts by weight of butyl acrylate, 5 parts by weight of 2-hydroxyethyl acrylate, 5 parts by weight of 2-hydroxy-2-butyl acrylate and 0.2 parts by weight of 1-hydroxycyclohexyl phenyl ketone were added to a reactor equipped with an electric stirrer, a thermometer, a nitrogen pipeline and a dry air pipeline. The equipment was connected and nitrogen was introduced into the reactor for 10 minutes to replace the dissolved oxygen in the reactor. At the same time, the electric stirrer was started at a speed of 300 rpm to stir the reactants in the reactor evenly. A high-pressure UV mercury lamp was used to irradiate the reactor at 1500 mj / cm 2 Energy irradiation, when the reaction temperature rises to 25-40°C (such as 25°C), stop irradiation, turn off nitrogen, and introduce dry air until the polymer temperature begins to drop, thereby obtaining an acrylate prepolymer.
[0079] (2) Preparation of OCA optical adhesive: Take 5 parts of trimethyl hexamethylene diisocyanate, 95 parts of acrylate prepolymer and 0.6 parts of 1-hydroxycyclohexyl phenyl ketone by weight, mix them evenly, degas in vacuum, and then apply the mixture between the light and heavy layers of polyethylene terephthalate (PET) release film. Use a high-pressure UV mercury lamp at 2000mj / cm 2 Energy irradiation, reaction to 810cm in infrared spectrum -1 Until the characteristic peak of the nearby acrylate double bond disappears, OCA optical glue with a thickness of 50μm is obtained.
[0080] Comparative Example 4 Comparative Example 4 refers to the method for preparing the OCA optical adhesive of Example 1, except that in step (1), the preparation of the oxime amine ester prepolymer is different.
[0081] Step (1) of Comparative Example 4 includes: Preparation of oxime urethane prepolymer: 55.57 g of isophorone diisocyanate and 0.09 g of dibutyltin dilaurate were added to a 250 mL four-necked jacketed reactor, the reactor was filled with 50 mL of tetrahydrofuran solution, equipped with an electric stirrer, a thermometer, a nitrogen pipeline and a serpentine condenser, the device was connected, nitrogen was introduced into the reactor for 10 minutes to replace the dissolved oxygen in the reactor, and the electric stirrer was started at 300 rpm to stir the reactants in the reactor evenly. The reaction temperature was controlled at 80°C. After the temperature was constant, 29.03 g of dimethylglyoxime was added to the reactor. After the dimethylglyoxime was completely dissolved, samples were taken every 30 minutes to react until the infrared spectrum showed 2268 cm -1 When the infrared characteristic peak area of NCO no longer changes, the reaction is stopped to obtain an oxime urethane prepolymer.
[0082] Experimental example 1. Dynamic mechanical testing (1) Storage modulus test Dynamic mechanical analysis is used to test the dynamic storage modulus. The rheometer used in the test is Anton Paar's MCR302 rheometer. During the test, the sample is cut into appropriate sizes, the stacking thickness is between 400 and 800 μm, the temperature scanning range is -45 to 80 ° C, the heating rate is 5 ° C / min, the frequency is 1 Hz, and the strain size is 0.1%. The shear storage modulus (G') is recorded at the selected specific temperature.
[0083] (2) Creep test Dynamic mechanical analysis is used to test the dynamic storage modulus. The rheometer used in the test is Anton Paar's MCR302 rheometer. During the test, the sample is cut into appropriate sizes, the stacking thickness is between 400 and 800 μm, and a shear stress of 20 kPa is applied for 10 minutes. At this time, the applied stress is removed and the sample is allowed to recover in the fixture for 10 minutes. The laminate sample is subjected to creep testing. The creep recovery rate at room temperature (25°C) exceeds 90%, the maximum strain exceeds 300%, the creep recovery rate at -20°C exceeds 85%, and the maximum strain exceeds 90%, which is qualified. Otherwise, it is unqualified.
[0084] The dynamic mechanical test results are shown in Table 1.
[0085] Table 1 Dynamic mechanical test results
[0086] 2. Optical performance test The clean test glass was calibrated, the OCA optical adhesive was cut to a suitable size, the light release film was removed and attached to the test glass, and then the heavy release film was removed. The transmittance and haze were tested according to the standard ASTMD1003. Each sample was repeated at least three times, and the test results were averaged. The test results are shown in Table 2.
[0087] Table 2 Dynamic mechanical test results
[0088] 3. Mechanical testing (1) 180° peel strength test The OCA optical adhesive coated and cured with the PET release film is cut into strips with a size of 100mm×25mm×150μm (length×width×thickness) with a cutter (the preparation of the specific OCA optical adhesive refers to the various embodiments and comparative examples to obtain strips with dimensions that meet the requirements), the light PET release film is peeled off and attached to the PET substrate, and then the heavy release film is peeled off and attached to the test glass, and a 2kg roller is used to roll back and forth three times at a speed of 300mm / min, and then degassing is carried out at 80℃ / 0.5MPa for 30min, and naturally cooled to room temperature, and tested according to the 180° peel strength test method for pressure-sensitive adhesive tapes and referring to GB / T2792-1998. Each sample is repeated at least three times, and the test results are averaged.
[0089] (2) Bonding reliability test The adhesive reliability test is carried out by testing the high temperature and high humidity aging performance of the peeling force test sample. According to GBT2423.3-2006 standard, the sample is placed in a constant temperature and humidity chamber at a temperature of 85°C and a relative humidity of 85%. After 1000 hours, the appearance is observed and the 180° peel strength test is performed. Each sample is repeated at least three times, and the test results are averaged. The appearance inspection method is to conduct an appearance inspection on the sample strips after the reliability experiment. The inspector visually inspects the finished product at an angle of 0 to 90° under ordinary light source (black background). The judgment criteria are whether there are bubbles and whether the edge is white. If there are no bubbles and the edge is not white, it is qualified; otherwise, it is unqualified. The test results are shown in Table 3.
[0090] Table 3 Mechanical test results
[0091] 4. Self-repair rate test The self-healing performance is characterized by the mechanical properties it recovers, and the test standards are consistent with the mechanical property tests.
[0092] Tensile mechanical properties test: The specimens were cut into standard length and width, and tested using the TH-8203A tensile testing machine of Suzhou Tuobo Mechanical Equipment Co., Ltd. in accordance with GB / T528-2009 standard. The tensile test was carried out at a constant rate of 100 mm / min at room temperature. Each sample was repeated at least three times, and the test results were averaged.
[0093] Self-repair rate test: On this basis, when doing the self-repair performance test, the sample is cut along the middle perpendicular to the tensile axis, the cross section of the sample is closely contacted at room temperature, and then it is self-repaired at 50°C. After repairing for different times, it is cooled to room temperature and then immediately subjected to a tensile test. Each sample is repeated at least three times for the tensile test, and the test results are averaged. The self-repair rate is characterized by the ratio of the elongation at break after repair to the elongation at break of the initial sample, and the calculation method is as follows: Self-repair rate = ε 修复后 / ε 初始 ×100% (ε represents the elongation at break, which is the average value of 3 tests). The test results are shown in Table 4.
[0094] Table 4 Self-repair rate test results
[0095] 5. Bending test (1) Static folding test Remove the light and heavy PET films of the test sample, and then paste the test substrate (folding screen test module) on both sides of the sample, set the bending angle to 180°, bend the sample to a curvature radius of approximately R=2.5mm and keep it bent for 240 hours at normal temperature and humidity (25℃, 50%RH). After 240 hours, observe whether the OCA optical adhesive and the test substrate maintain their original state. If there are no creases, bubbles, and delamination between the test sample and the substrate, it means that the sample has passed the static holding test, otherwise it has failed.
[0096] (2) Dynamic folding test The light and heavy PET films of the test sample were removed, and then the test substrate (folding screen test module) was attached to both sides of the sample. The sample was fixed in the folding device, bent from 0° to 180° at a constant rate, and 150,000 cycles were performed at a test rate of about 60 times / minute. The bending radius R=2.5mm, and the test was performed at room temperature and humidity (25°C, 50%RH). After 150,000 cycles of bending, observe whether the OCA optical glue and the test substrate maintain the original state. If there are no creases, bubbles, and delamination between the test sample and the substrate, it means that the sample has passed the dynamic holding test, otherwise it has failed. The test results are shown in Table 5.
[0097] Table 5 Bending test results
[0098] According to the above test results, the low temperature (-20°C) storage modulus of the OCA optical adhesive of the embodiment of the present invention is less than 30KPa, the room temperature (25°C) storage modulus is less than 3KPa, and the room temperature creep recovery rate exceeds 90%, the maximum strain exceeds 300%, the -20°C creep recovery rate exceeds 85%, and the maximum strain exceeds 90%. In addition, it exhibits high light transmittance, good adhesion, high self-repair rate and excellent bending resistance.
[0099] The amount of oxime amine prepolymer added in Comparative Example 1 is relatively large, and the creep test result of the corresponding OCA optical adhesive is unqualified; and, in the mechanical property test, the peel strength is too large, and part of the colloid sticks to the glass substrate and cannot be peeled off during the test, resulting in sample damage; in the self-repair test, the corresponding test results are not much different from the OCA optical adhesive in the embodiment.
[0100] Through comparative analysis of the test results of various embodiments and comparative examples, it can be known that the present invention introduces an appropriate amount of dynamically cross-linkable oxime amine ester structure into the OCA optical adhesive, which not only enables the OCA optical adhesive to have good self-repairing properties without affecting the light transmittance, but also exhibits good adhesion to the substrate, which is beneficial to improving the reworkability of the OCA optical adhesive during use, and can achieve OCA optical adhesive with high flexibility, high bending resistance, high weather resistance, strong creep and self-repairing properties, thereby effectively improving the service life of the OCA optical adhesive and maintaining long-term reliability for daily use, so as to solve the problems of creases, bubbles, lamination delamination, etc. that occur during the long-term use of folding screens in complex environments, and effectively extend the service life.
[0101] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. An OCA optical adhesive with strong creep resistance, low storage modulus and self-repairing function, characterized in that: It includes acrylate prepolymer, oxime urethane prepolymer and a first initiator; The mass ratio of the oxime urethane prepolymer to the acrylate prepolymer is (1-5): (95-100); The oxime urethane prepolymer is mainly prepared by the reaction of trimethylhexamethylene diisocyanate and a dioxime compound.
2. The OCA optical adhesive according to claim 1, characterized in that: The trimethyl hexamethylene diisocyanate includes at least one of 2,2,4-trimethyl hexamethylene diisocyanate and 2,4,4-trimethyl hexamethylene diisocyanate.
3. The OCA optical adhesive according to claim 1, characterized in that: The trimethyl hexamethylene diisocyanate comprises 2,2,4-trimethyl hexamethylene diisocyanate and 2,4,4-trimethyl hexamethylene diisocyanate in a mass ratio of 1:(0.5-2).
4. The OCA optical adhesive according to claim 1, characterized in that: The dioxime compound includes at least one of dimethylglyoxime, 2,4-pentanedione dioxime and p-benzoquinone dioxime.
5. The OCA optical adhesive according to claim 1, characterized in that: The molar ratio of the trimethylhexamethylene diisocyanate to the dioxime compound is 1:(0.95-1.05).
6. The OCA optical adhesive according to claim 1, characterized in that: The acrylate prepolymer is mainly prepared by polymerizing acrylate monomers under the initiation of a second initiator; the acrylate monomers include the following components by weight: 60 to 80 parts of 2-ethylhexyl acrylate, 5 to 10 parts of butyl acrylate and 10 to 20 parts of hydroxyl-containing acrylate; The hydroxyl-containing acrylate includes at least one of 2-hydroxyethyl acrylate and 2-hydroxy-2-butyl acrylate.
7. The OCA optical adhesive according to claim 6, characterized in that: The amount of the second initiator is 0.2wt% to 1wt% of the total amount of the acrylic ester monomer; The second initiator includes at least one of 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenylpropanone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide and benzoin dimethyl ether.
8. The OCA optical adhesive according to claim 1, characterized in that: The amount of the first initiator is 0.2wt% to 1wt% of the sum of the mass of the acrylate prepolymer and the oxime urethane prepolymer; The first initiator includes at least one of 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenylpropanone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide and benzoin dimethyl ether.
9. The OCA optical adhesive according to claim 1, characterized in that: The thickness of the OCA optical adhesive is 25-200 μm.
10. A method for preparing OCA optical adhesive, characterized in that: The method comprises the following steps: according to the composition of the OCA optical adhesive described in any one of claims 1 to 9, acrylate prepolymer, oxime urethane prepolymer and a first initiator are mixed in proportion, coated into a film, and then cured by ultraviolet radiation.
Citation Information
Patent Citations
OCA with high light transmittance, low storage modulus and self-repairing function and preparation method thereof
CN112920763A
Oxime ammonia ester modified self-repairing high-gloss hydroxypropyl dispersion and preparation method thereof
CN119409900A
Adhesive sheet
JP2021084931A